From the structural crisis of the pattern of world, colonial, modern, and capitalist power toward economic solidarity and good living in Latin America - Marañón, Boris (Cooperativismo & Desarrollo, 2016)
Purpose: This article seeks to guide solidarity thinking and practices from a perspective that transcends economic and ethical concerns. Description: Included are not only the power relations that sustain life in capitalist society, but also the need for awareness that we are facing a dramatic epoch shift. Both the progress/development and modernity projects are undergoing irreversible crises, and wemust prioritize taking care of life. Viewpoint: To this end, the concept of economic solidarity is put forward, which allows—assuming economic and cultural diversity—the linking of all practices inspired by liberating and solidarity rationales. Going beyond their possible assignment to certain ethical, political, andcultural schools of thought or to specific institutional forms, these rationales are based on reciprocity, decommodification, and self-government. They are also as sociated with a new horizon: good living, or, good livings oriented toward de coloniality. Conclusions: It should be noted that the struggle for an alternativesociety is not only an economic and ethical struggle; the current structural crisis encompasses an entire historical form of human coexistence and the whole pattern of colonial-modern and capitalist power.
Keywords: good living; decoloniality of power; economic solidarity